Rain influences the physiological and metabolic responses to exercise in hot conditions - Ito, R.; Yamashita, N.; Suzuki, E.; Matsumoto, T. (Journal of Sports Sciences, 2015)
Outdoor exercise often proceeds in rainy conditions. However, the cooling effects of rain on human physiological responses have not been systematically studied in hot conditions. The present study determined physiological and metabolic responses using a climatic chamber that can precisely simulate hot, rainy conditions. Eleven healthy men ran on a treadmill at an intensity of 70% VO2max for 30 min in the climatic chamber at an ambient temperature of 33°C in the presence (RAIN) or absence (CON) of 30 mm/h of precipitation and a headwind equal to the running velocity of 3.15 ± 0.19 m/s. Oesophageal temperature, mean skin temperature, heart rate, rating of perceived exertion, blood parameters, volume of expired air and sweat loss were measured. Oesophageal and mean skin temperatures were significantly lower from 5 to 30 min, and heart rate was significantly lower from 20 to 30 min in RAIN than in CON (P < 0.05 for all). Plasma lactate and epinephrine concentrations (30 min) and sweat loss were significantly lower (P < 0.05) in RAIN compared with CON. Rain appears to influence physiological and metabolic responses to exercise in heat such that heat-induced strain might be reduced